Pengaruh Motivasi dan Pendidikan Kewirausahaan Terhadap Kesiapan Mahasiswa Sebagai Enterpreneurship di Era Globalisasi Pada Mata Kuliah Manajemen Usaha Boga - Gusnita, Wiwik; Ganefri; Yulastri, Asmar; Giatman; Muskhir, Mukhlidi; Effendi, Hansi (The Indonesian Journal of Computer Science, 2023)
D3 Culinary Arts Study Program students are targeted to become graduates who are able to have an entrepreneurial spirit. Basically, building a business requires high motivation to be able to compete with other entrepreneurs. This research aims to see the influence of motivation and entrepreneurship education on students' readiness for entrepreneurship in the Catering Business Management course after completing their studies. The method used in this research is a quantitative descriptive method with correlation studies. The correlation analysis technique in this research uses the product-moment correlation statistical test using interval data with certain conditions. The coefficients table shows that the significance value of the motivation variable (X1) does not have a significant effect on variable Y (student readiness), namely 0.085 > 0.05. Meanwhile, variable X2 (entrepreneurship education) has a significant effect on variable Y (student readiness), namely 0.000 < 0.05. It can be concluded that with entrepreneurship education, students are ready to become entrepreneurs by having knowledge of business production management, knowing procedures, understanding how to produce businesses, and how to develop ideas.